2006
DOI: 10.1590/s1677-55382006000600005
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the renal pelvis and ureter

Abstract: A high association was also found between UUTT and bladder urothelial carcinoma. UUTT were mostly seen in men in their seventies and related to a high overall and cancer-related mortality rate. The overall disease-specific survival was 40%, much lower than found in most of the reported series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Urothelial carcinoma (UC) of the ureter and renal pelvis is relatively uncommon, accounting for only 5-6% of all urothelial tumours [1,2]. Two groups have assessed the trends in incidence of upper urinary tract (UUT) tumours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urothelial carcinoma (UC) of the ureter and renal pelvis is relatively uncommon, accounting for only 5-6% of all urothelial tumours [1,2]. Two groups have assessed the trends in incidence of upper urinary tract (UUT) tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Data on distribution of stage and grade at initial presentation indicate that most patients present with a low stage (Ta-T1) grade 2 or 3 tumour [1,[6][7][8][9]. Stage and grade are the most important prognostic factors for recurrence and survival [7][8][9][10][11], but type of treatment [7] and multifocality [8,12], have also been reported to be important, to a variable extent.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to bladder cancer, significantly fewer studies have discussed the connection between UTI and renal pelvis/ureter cancer because of its relative rarity. Studies regarding this issue showed either non‐significant findings or inconclusive results …”
mentioning
confidence: 99%
“…Studies regarding this issue showed either non-significant findings (13) or inconclusive results. (14) Several mechanisms were proposed for explaining the association between infection and bladder cancer. (11,12) First, chronic inflammation of the bladder may induce urinary retention and stasis, which can potentially increase exposure and absorption of carcinogens present in the urine.…”
mentioning
confidence: 99%
“…Urothelial carcinomas are more closely associated with lifestyle factors, whereas non-urothelial carcinoma bladder cancers are often associated with infections, foreign bodies or invasive cancers from neighboring organs (16). Ninety percent of all cancers that occur in the bladder (17)(18)(19) and in the urothelium of the upper urinary tract (20) are urothelial carcinoma. Due to the common epithelium of origin, all urothelial carcinoma have similar risk factors (18,21).…”
Section: Introductionmentioning
confidence: 99%